FINANCING BUSINESS ON ISLAMIC PRINCIPLES: AN ETHICAL AND SUSTAINABLE APPROACH - Valijonov Kh.B (American Journals, 2023)
Islamic finance has attracted interest in recent decades as an alternative financial system that works according to Islamic principles. This article examines the concept of financing a business on Islamic principles and its potential benefits for ethical and sustainable economic growth. We discover the basic principles of Islamic finance, such as the Prohibition of interest (Riba), the Prevention of excessive uncertainty (garar) and the demand for the exchange of profit and loss (Mudarabah). In addition, we will analyze various Islamic financing tools, including Musharakah, Murabahah and Ijarah, and highlight their practical applications for business financing. We discuss the potential benefits of Islamic finance, including social responsibility, promotion of fair wealth distribution, and resilience to financial crises. We will also solve the problems faced in the implementation of Islamic financing principles and explore the paths for further research. Islamic finance has gained much attention in recent years due to its ethical and inclusive nature. However, its implementation and adoption are faced with a number of problems that hinder its growth potential. This article highlights key obstacles such as standardization of sharia compliance, development of competitive human resources and elimination of misconceptions related to the Islamic financial sector. It also emphasizes the importance of continuous research and innovation to overcome these challenges and further boost the growth of Islamic finance.